Komik Dagusibu Untuk Meningkatkan Pengetahuan Obat Siswa-Siswi Sekolah Dasar Negeri - Pratiwi, Rani Dewi (Ilin Institute, 2025)
This community service aims to increase knowledge about the Dagusibu program to the community, especially elementary school children at SD Negeri 3 Abepura so that they understand medicine, namely how drugs are obtained, used, stored, and disposed of. The method of service is action research. Participants in the service activities were 5th-grade students of SD Negeri 3 Abepura, namely 37 students. This service activity uses comic media to convey knowledge about dagusibu medicine, measuring the success of activities using questionnaire instruments given before and after the material is provided. Measurement of increased knowledge about dagusibu by calculating the number of correct questions on the questionnaire before and after the activity. The results of the service showed an increase in knowledge about Dagusibu in students of SD N 3 Abepura, namely an increase in knowledge of how to get medicine by 16%, how to use medicine by 22%, how to store medicine by 30% and how to dispose of medicine by 60%. This service concludes that there is increased knowledge about dagusibu medicine in SD Negeri 3 Abepura students.